Evaluation of culture conditions for osteoclastogenesis in RAW264.7 cells - Cheng, Yin; Liu, Haixia; Li, Jing; Ma, Yujie; Song, Changheng; Wang, Yuhan; Li, Pei; Chen, Yanjing; Zhang, Zhiguo (PLOS ONE, 2022)
Osteoclasts are the only multinucleated cells in vivo responsible for bone resorption and are vital for regulating bone remodeling and maintaining bone mass. The RAW264.7 cell line is widely used to study osteoclastic differentiation and biological molecular mechanism. However, protocols for inducing osteoclast formation in RAW264.7 cells vary considerably between laboratories, hindering the replication of results. Therefore, we tested the influence of culture conditions on osteoclast differentiation, including cell density and receptor activator of nuclear factor kappa-B ligand (RANKL) concentrations with or without macrophage colony-stimulating factors (M-CSF). Tartrate-resistant acid phosphatase (TRAP) staining was used to detect the morphology of osteoclasts. qPCR was used to detect gene expression of osteoclast-specific gene marker cathepsin K (CTSK), osteoclast transcription factors c-Fos and nuclear factor of activated T cells, cytoplasmic 1 (NFATc1). The bone resorption function was evaluated by a scanning electron microscope (SEM). RANKL treatment increased multinucleated osteoclasts formation and increased CTSK, c-Fos and NFATc1 gene expression. Compared with RANKL treatment, M-CSF significantly decreased multinucleated osteoclasts formation, reduced CTSK gene expression and had little effect on c-Fos and NFATc1 gene expression. Concerning bone resorption activity, RANKL treatment increased bone resorption pits on bovine bone slices. Significantly higher levels of osteoclastogenesis were observed with RAW264.7-cell density of 2×104 cells/well in 24-well plates. Our results suggest that the addition of 50 ng/ml M-CSF has no positive effect on osteoclastogenesis. RANKL treatment and cell density contribute to osteoclast formation, and the optimal conditions are beneficial when exploring osteoclast function and mechanism.